(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Research on renewable energy based Electric Vehicle battery charging system is booming in the automobile industry in recent years. The intermittent nature of the renewable energy sources leads to the grid connected renewable energy systems for Electric Vehicle battery charging applications. In this paper, a photovoltaic array-fed off-board battery charging system using a bidirectional interleaved DC-DC converter is proposed for light-weight electric vehicles. This off-board charging system is capable of operating in dual mode, thereby supplying power to the electric vehicles battery from the photovoltaic array in standstill conditions and driving the DC load by the electric-vehicle battery during running conditions. This dual mode operation is accomplished by the use of a three-phase bidirectional direct-current. The model of the proposed system is simulated in MATLAB/Simulink software.